A Janus‐type Heterogeneous Surfactant for Adipic Acid Synthesis. Issue 10 (1st April 2020) - Vafaeezadeh, Majid; Wilhelm, Christian; Breuninger, Paul; Ernst, Stefan; Antonyuk, Sergiy; Thiel, Werner R.
Abstract: A highly water‐dispersible heterogeneous Brønsted acid surfactant was prepared by synthesis of a bi‐functional anisotropic Janus‐type material. The catalyst comprises ionic functionalities on one side and propyl‐SO3 H groups on the other. The novel material was investigated as a green substitute of a homogeneous acidic phase transfer catalyst (PTC). The activity of the catalyst was investigated for the aqueous‐phase oxidation of cyclohexene to adipic acid with 30 % hydrogen peroxide even in a decagram‐scale. It can also be used for the synthesis of some other carboxylic acid derivatives as well as diethyl phthalate. Abstract : Heterogeneous surfactant : A novel surfactant‐like heterogeneous Janus nano‐catalyst is applied for the decagram‐scale synthesis of adipic acid from the oxidation of cyclohexene with hydrogen peroxide. The catalyst was also used for the oxidation of other compounds to carboxylic acid derivatives as well as the synthesis of diethyl phthalate by esterification of phthalic anhydride with ethanol.